Status and Forms of Calcium in Two Arable Farms: An Assessment of Soil Fertility and Nutrient Availability - Bakare, A. O. (2024)
This study investigated the status and forms of calcium in two arable farms, Yam and Cassava farms (Dioscorea rotundata and Manihot esculenta Crantz), under two different land use systems. Soil samples were collected from four depths (0 cm -30 cm, 30 cm -60 cm, 60 cm -90 cm, and 90 cm -120 cm), and for analyzed physical and chemical properties, including calcium fractions: exchangeable, non-exchangeable, and mineral-bound calcium. The results showed that soil pH decreased with depth in both farms, ranging from 5 to 4.07 in Yam Farm and 4.50 to 3.90 in Cassava Farm. The results also showed significant decreases in exchangeable calcium with depth in both farms, ranging from 0.34 mg.kg-1 to 0.06 mg.kg-1 in Yam Farm and 0.42 mg.kg-1 to 0.05 mg.kg-1 in Cassava Farm. The study revealed significant correlations between exchangeable calcium and other soil properties, including electrical conductivity, sand content, organic carbon, and available phosphorus. The impact of the two land use systems on soil calcium fractions and properties was significant, with Yam Farm showing higher levels of exchangeable calcium and organic carbon than Cassava Farm. The study highlights the importance of considering the impact of different land use systems on soil calcium fractions and properties to maintain soil fertility and support sustainable agriculture.